Applying Analysis: Towards Addressing Violence in Non-Credit Feminist Learning Contexts with Differently Located Women - McKenzie, Christine (Atlantis, 2010)
This paper explores the unconscious role that educators may play in perpetuating subtle violence in feminist non-credit learning spaces with differently located women. Following this analysis I offer issues with which educators can engage in order to analyse and address these ongoing forms of systemic violence in their praxis.